Evaluation of metabolism and biosignaling in the angiogenic microenvironment as potential targets for therapeutic intervention - Medina-Torres, Miguel Ángel; Ocaña Farfán, María del Carmen; Martínez-Póveda, Beatriz Amparo; Carrillo Fernández, Paloma; Urdiales-Ruiz, José Luis; Serrano, José J.; Montañez, Raúl; Rodríguez-Quesada, Ana María (My University, 2017)
The "re-discovery" of Warburg effect at the turn of the present millennium has been a key determinant of the current renewed interest on cancer metabolism. In fact, metabolic reprogramming has been identified as one of the hallmarks of cancer. However, cancers grow in tight contact with non-tumoral accompanying cells and the surrounding extracellular matrix, as underlined by the concept of tumor microenvironment. Endothelial cells are key components of this tumor microenvironment, since they are requested for angiogenesis, another hallmark of cancer. In this complex system, rewiring of metabolism and signaling pathway in cancer, endothelial and other accompanying cell emerges as new potential targets for therapeutic intervention. In this communication, we will present the drug discovery and characterization approach of our group and our more recent results in this field, including new modeling with an evolutionary and ecological point of view.
Keywords: Cáncer; Cancer; Angiogenesis; Metabolism; Microenvironment